2021
DOI: 10.1002/jso.26515
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid expansion and the management of pancreatic cancer

Abstract: Background: Medicaid expansion under the Affordable Care Act has improved access to screening and treatment for certain cancers. It is unclear how this policy has affected the diagnosis and management of pancreatic cancer.Methods: Using a quasi-experimental difference-in-differences (DID) approach, we analyzed Medicaid and uninsured patients in the National Cancer Data Base during two time periods: pre-expansion (2011-2012) and postexpansion (2015-2016). We investigated changes in cancer staging, treatment dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A key aspect of the DID approach is the assumption of parallel trends between ME and NE states in the pre‐2014 period 23 . The parallel trends assumption was first assessed with visual inspection of unadjusted trends and by conducting a falsification test by fitting a regression model for each outcome that included an interaction term between state expansion status and diagnosis year during the pre‐expansion period, as done in prior DID studies 17,19,20,24–29 . Year by expansion group interaction terms for TTI outcomes were not statistically significant for nearly all cancer types except for breast cancer.…”
Section: Methodsmentioning
confidence: 99%
“…A key aspect of the DID approach is the assumption of parallel trends between ME and NE states in the pre‐2014 period 23 . The parallel trends assumption was first assessed with visual inspection of unadjusted trends and by conducting a falsification test by fitting a regression model for each outcome that included an interaction term between state expansion status and diagnosis year during the pre‐expansion period, as done in prior DID studies 17,19,20,24–29 . Year by expansion group interaction terms for TTI outcomes were not statistically significant for nearly all cancer types except for breast cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Medicaid expansion has been associated with earlier diagnoses, fewer treatment delays, and more treatment options being available for patients with cancer. An association between Medicaid expansion and an increase in early-stage diagnoses has been reported in patients with breast cancer [30], squamous cell carcinoma of the head and neck [31], gynecologic cancer [32], intrahepatic cholangiocarcinoma [33], hepatocellular carcinoma [34], gastric cancer [35], kidney cancer [36], pancreatic cancer [37], and melanoma [38]. Medicaid expansion has also been associated with an improved time in the initiation of treatment for Black and Hispanic patients with early-stage breast cancer who require adjuvant chemotherapy [39], and for patients with non-oropharyngeal HNSCC [40] and gynecologic cancers [32].…”
Section: Enhanced Quality Of Carementioning
confidence: 99%
“…4,12,13 In contrast, other investigators have failed to confirm an association between ME and early diagnosis for pancreatic cancer. 13,14 To date, the impact of ME implementation on BTCs care has not been well defined. As such, the objective of the current study was to define the impact of ME on receipt of multimodal care, including surgical resection, for stage I-III BTC utilizing a nationwide cohort.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous research on pancreatic adenocarcinoma (PDAC) and intrahepatic cholangiocarcinoma (ICC) demonstrated an association between ME and better access to surgical and palliative therapies, as well as increased early cancer detection and improved outcomes 4,12,13 . In contrast, other investigators have failed to confirm an association between ME and early diagnosis for pancreatic cancer 13,14 . To date, the impact of ME implementation on BTCs care has not been well defined.…”
Section: Introductionmentioning
confidence: 99%